2010
DOI: 10.4103/0976-7800.76220
|View full text |Cite
|
Sign up to set email alerts
|

Acute abdomen with hemoperitoneum in a postmenopausal woman

Abstract: Gynecological emergencies may be encountered in postmenopausal ladies like that of ruptured ectopic pregnancy in the reproductive age group. We report a case of ruptured granulosa cell tumor in a 70-year-old woman who presented with acute abdomen and hemoperitoneum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Granulosa cell tumors grow to be highly vascular, making them prone to hemorrhagic rupture [3] . Patient presentation of a hemorrhagic GCT is nonspecific and does not always present as hemorrhagic shock [11] , [12] , [13] . The differential diagnosis for spontaneous intra-abdominal bleeding includes splenic rupture, ruptured ovarian cysts, ectopic pregnancy, ruptured abdominal aorta aneurysms and visceral artery aneurysms, and pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Granulosa cell tumors grow to be highly vascular, making them prone to hemorrhagic rupture [3] . Patient presentation of a hemorrhagic GCT is nonspecific and does not always present as hemorrhagic shock [11] , [12] , [13] . The differential diagnosis for spontaneous intra-abdominal bleeding includes splenic rupture, ruptured ovarian cysts, ectopic pregnancy, ruptured abdominal aorta aneurysms and visceral artery aneurysms, and pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Acute abdomen with haemoperitoneum is a common gynaecological emergency but is rare in postmenopausal women. The diagnosis is more difficult to make in postmenopausal women as compared to those in reproductive age [ 1 , 7 ]. According to literature, the rupture of a granulosa cell tumour (GCT) of the ovary is a rare but possible reason of haemoperitoneum due to the high vascularity of the mass, with an estimated rate of 10% [ 8 , 9 ] to 15–17.6% [ 1 , 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients might also report a reduction in vasomotor symptoms because of suppressed FSH by high oestrogen levels [ 7 ]. In uncertain cases testing for FOXL2 mutation can help with diagnosis, as 97% of adult GCT showed mutation of this gene [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al reported that tumor rupture occurred in 17.6% of cases before surgery diagnosed as adult granulosa cell tumor but the pain did not present as a cause of acute abdomen [ 1 ]. To the best of our knowledge, there are four cases of hemoperitoneum because of ruptured granulosa cell tumor [ 2 – 5 ]. We report a 54-year-old postmenopausal woman who presented with acute abdomen and hemoperitoneum because of ruptured granulosa cell tumor.…”
Section: Introductionmentioning
confidence: 99%